Analisis Strategi Pemasaran Kredit Usaha Rakyat (KUR) Pada Bank Mandiri Cabang Barru - Jabal Rahmah; St Rukaiyah (STIM-LPI Makassar, 2026)
KUR) at Bank Mandiri Barru Branch and to formulate strategies for optimizing credit distribution to MSMEs. This study is crucial for identifying the supporting and inhibiting factors of the bank's strategy in facing local competition. The research method employed a descriptive qualitative approach, with data collection conducted through observation, interviews, and documentation. Data analysis techniques applied the concept of the Marketing Mix (7P) and SWOT Analysis, along with calculations of the IFAS, EFAS, and IE Matrix to determine the strategic position. The results place Bank Mandiri Barru Branch in the Grow and Build position (Cell II), characterized by a high external response but average internal conditions. The implementation of the Marketing Mix 7P was assessed as effective in product and technology aspects, yet constrained by human resource limitations. Recommended strategies include aggressive market penetration, expansion of the Laku Pandai agent network, and optimization of digital services to increase customer outreach